2018
DOI: 10.17235/reed.2018.5399/2017
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ distribution and risk assessment of celiac disease in a Spanish center

Abstract: there are four genetic risk categories according to the HLA-DQ genotype. The HLA-DQ7.5 genotype does not confer risk but should not be used to rule out celiac disease when a high suspicion of the disease exists. These findings could be relevant to determine when to perform serological screening in asymptomatic subjects at risk of celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Community‐based studies suggest that specific HLA‐DQB1 and ~DQA1 haplotypes confer approximately 5‐fold higher risk for CeD when compared to the absence of these haplotypes 14,16–19 . Among the healthy controls, the DQ2.5, DQ2.2, and DQ8.1 haplotypes were found in 11, 20, and 11%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Community‐based studies suggest that specific HLA‐DQB1 and ~DQA1 haplotypes confer approximately 5‐fold higher risk for CeD when compared to the absence of these haplotypes 14,16–19 . Among the healthy controls, the DQ2.5, DQ2.2, and DQ8.1 haplotypes were found in 11, 20, and 11%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The DQ2.2 haplotype is a low risk haplotype in CD patients in many countries [ 21 , 24 , 41 , 42 ]. In our study, predicted homozygous DQ2.2 was more frequent in control group (5.82%) than in cases (0.99%).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of disease association studies, it has been suggested that risk conferred by HLA can differ between distinct populations ( Ortiz-Fernández et al, 2014 ; Martínez-Ojinaga et al, 2018 ). A population-wise descriptive list of HLA alleles (at low resolution) as increased or decreased risk variants in disease phenotypes and disease progression in sarcoidosis has been outlined ( Kishore and Petrek, 2013 ; Fingerlin et al, 2015 ).…”
Section: Ngs Based Hla Typing In Population Studies and Its Applicatimentioning
confidence: 99%
“…Coeliac disease represents another example of a HLA associated disease with various European populations. This disease associates with HLA-DQA and - DQB genes and about 96% of European coeliac patients carry the HLA-DQ2.5 heterodimer ( DQA1 ∗ 05 - DQB1 ∗ 0201 ) ( Karell et al, 2003 ; Martínez-Ojinaga et al, 2018 ; Núñez et al, 2018 ) and in some reports differed among non-Europeans, for e.g., in Brazilians and Iranians, -DQ2.2 was not associated with coeliac disease ( Rostami-Nejad et al, 2014 ; Selleski et al, 2018 ). Also, the differential HLA basis of the GIMAP locus, which encoded proteins involved in the development of T and B lymphocytes, and Behçet’s disease was described in Asian and European populations ( Ortiz-Fernández et al, 2014 ).…”
Section: Ngs Based Hla Typing In Population Studies and Its Applicatimentioning
confidence: 99%